Buzzed : The straight facts about the most used and abused drugs from alcohol to ecstasy - Kuhn, Cynthia; Swartzwelder, Scott; Wilson, Wilkie (New York, United States of America : Norton & Company, Inc., 2003)
This book arose from our recognition of how little most adolescents, parents, lawmakers, and even medical advisrs know about drugs that we regularly use and abuse.
Part I Aocohol Caffeine Ecstasy Hallucinogens Herbal Drugs Inhalants Marijuana Nicotine Opiates Sedatives Steroids Stimulants Part II Brain Basics Drugs Basics Addiction Legal Issues Further Reading
Incluye Contents, Glossary of Drug-Related Street Terms/Slang Words, Index
Keywords: DRUGS; DROGAS; ALCOHOL; HALLUCINOGENS; MARIHUANA; ESTEROIDES